The effect of the employment of experienced physicians in the Emergency Department on quality of care and equality—a quasi-experimental retrospective cohort study. (22nd September 2021) - Lindstroem, Mette; Andersen, Ove; Kallemose, Thomas; Rasmussen, Line Jee Hartmann; Rosthoej, Susanne; Jervelund, Signe Smith
Abstract: Background: Increasing acute admissions in Emergency Departments (EDs) negatively affect quality of care, safety and flow. Thus, the Danish Health Authorities recommend the presence of experienced physicians in the ED. In 2016, consultant-led triage and continuous presence of consultants were introduced at a larger ED in Copenhagen, Denmark. This study investigated whether the employment of consultants in a Danish ED affected the quality of care for acutely admitted medical patients in terms of length of admission, readmission and mortality, as well as socioeconomic equality in quality of care delivery. Methods: Admission data were collected during two 7-month periods, one prior to and one after the organizational intervention, with 9869 adult medical patients admitted for up to 48 h in the ED. Linear regression and Cox proportional hazards regression analyses adjusted for age, sex, comorbidities, level of education and employment status were applied. Results: Following the employment of consultants, an overall 11% increase in index-admissions was observed, and 90% of patients were discharged by a consultant with a reduced mean length of admission by 1.4 h (95% CI: 1.0–1.9). No change was found in in-hospital mortality, readmission or mortality within 90 days after discharge. No change in distribution of quality indicators across patients' socioeconomic status was found. Conclusions: Consultants in the ED was found to reduce length of hospitalization without a negative effect on the quality of care for ED-admitted medical patients in general or patients with lower socioeconomic status.